(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to determine the effect of two different doses of methylprednisolone administered in our emergency department (ED) on the elapsed time in biphasic or recurrent anaphylaxis cases.Materials and Methods: The patients with anaphylaxis admitted to the ED were retrospectively analyzed. A total of 82 patients who received methylprednisolone in combination with epinephrine in the ED due to anaphylaxis and who developed biphasic reaction within 48 h after discharge were included in the study. The patients were classified into two groups according to the dose of methylprednisolone administered: 80 mg (Group 1, low-dose) and 120 mg (Group 2, high-dose). The effect of different doses of methylprednisolone on the development time of biphasic reaction was evaluated.Results: Two different doses of IV methylprednisolone administered in the ED did not affect the development time of biphasic reaction (p = 0.24). The biphasic reaction development times were 335 (IQR, 212–950) min in the low-dose group and 520 (IQR, 265–1150) min in the high-dose group. The earliest development time of biphasic reaction was 125 min (low-dose group) and the latest development time was 2270 min (high-dose group). The relationship between dose and biphasic reaction development times was evaluated using Kaplan–Meier curve. No significant difference was observed between the two groups (p = 0.28). Upon comparing the symptoms in patients’ second admission to the ED due to biphasic reaction, no statistically significant difference was observed in patient symptoms with respect to the dose administered (p > 0.05).Conclusions: Corticosteroids are often used in ED, although there is no definitive evidence that they prevent biphasic reactions. The administration of two different doses of methylprednisolone has no effect on biphasic reaction development time.